Mapping Through Stories - Nadal, Cathe Desiree S. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2023)
Landscape Walking Narratives (LWN) is a landscape-based mapping procedure that came from the PhD research project entitled, “Capturing the Dynamic Character of the Philippine Peri-urban Landscape: A Landscape Character System Approach for the Region of Cavite" (2021). The LWN used a walkers-based cataloging procedure to collect cultural landscape narratives from walkers. LWN also incorporated oral history methodologies to find intangible cultural landscape features, resulting in landscape word clouds and graphs. This mapping approach pushed the boundaries of landscape characterization by demonstrating the ability to translate narratives into meaningful data formats to help in future planning decisions for Cavite.